Sport Coaching Concepts / A Framework for Coaching Practice: Second Edition - Cushion Chris; Lyle John (Routledge - Taylor & Francis Group, 2003)
Introduction to the Second Edition, Developments in the Field, Developing a Conceptual Framework, The Coaching Process, Coaching Domains and the Role of the Coach, Expertise in Sport Coaching, Modelling the Coaching Process, A Proposed Model for Coaching, Operationalising the Model; Or and What Coaches Really Do!, Approaches to Coaching Practice: Linking Theory and Practice, Coaching and Social Context, Coaching Philosophy, Pedagogy in Practice, The Professionalisation of Sport Coaching, Coach Education and Coaching Practice, Setting a Research Agenda, Index.